2021
DOI: 10.1186/s12913-021-06799-1
|View full text |Cite|
|
Sign up to set email alerts
|

Role of financial incentives in family planning services in India: a qualitative study

Abstract: Background In an effort to encourage Family Planning (FP) adoption, since 1952, the Government of India has been implementing various centrally sponsored schemes that offer financial incentives (FIs) to acceptors as well as service providers, for services related to certain FP methods. However, understanding of the role of FIs on uptake of FP services, and the quality of FP services provided, is limited and mixed. Methods A qualitative descriptive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…PPIUD uptake and continuation among women in LMIC contexts have been shown to require multi-layered and multi-dimensional interventions [ 38 ]. Many studies from India have highlighted the key role of partners and family members in the decision to take up and use a family planning method [ 30 , 39 , 40 ]. Our study also found that some participants opted for removal primarily because of their partner’s/husband’s disapproval.…”
Section: Discussionmentioning
confidence: 99%
“…PPIUD uptake and continuation among women in LMIC contexts have been shown to require multi-layered and multi-dimensional interventions [ 38 ]. Many studies from India have highlighted the key role of partners and family members in the decision to take up and use a family planning method [ 30 , 39 , 40 ]. Our study also found that some participants opted for removal primarily because of their partner’s/husband’s disapproval.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], multiple language errors were identified because the typesetter didn’t implement these corrections during production. The changes have been highlighted with corrections and shown in Additional file 1.…”
mentioning
confidence: 99%